Covid-19 associated pulmonary aspergillosis with extensive cavitary pneumonia: a case report - Hanif, Sadaf; Iqbal, Madiha; Sethi, Sher Muhammad (Journal of the Pakistan Medical Association, 2022)
Covid-19 associated pulmonary aspergillosis (CAPA) is a new entity and is associated with high morbidity and mortality. Covid-19 is a pro-inflammatory and immunosuppressive disease, provoking fungal infections, especially by Aspergillus species. We describe the case of a critically ill Covid-19 female patient, who was diagnosed with CAPA infection and acute respiratory distress syndrome (ARDS). She was given intravenous Remdesivir. Her chest X-ray a few days after admission showed multiple cavities. Her condition initially improved but deteriorated again, with worsening hypoxia and pneumothorax and multiple cavitary lesions on HRCT of the chest. Despite optimal treatment, she could not recover. Interestingly, she had no predisposing risk factor for pulmonary aspergillosis, such as chronic lung disease, diabetes or use of immunosuppressants such as Tocilizumab. CAPA is an emerging entity with worsening hypoxia, and failure to improve can be an early sign. Early identification and treatment can improve survival and outcomes in Covid-19 patients.